Fluid motion mathematical model development in a partially filled cavity - Kemenyash, Yu. M. (Electronics and Control Systems, 2016)
The solution of the problem of oscillations of a fluid in the cavities with a rectilinear generatorat different levels of completion. Parameter calculation results obtained pendulum model for longitudinalfluid oscillations